Kebijakan dan Implementasi Manajemen Pembiayaan dalam Meningkatkan Mutu Pendidikan di MTs Sains Qurani Azzakiyyah Cinunuk Kabupaten Bandung - Amaliyah, Kholishotul (STAI Al Badar Cipulus Purwakarta, 2024)
Education plays a crucial role in societal development, and financial management holds a central position in enhancing educational quality. This scholarly article investigates the policies and implementation of financial management at MTs Sains Qurani Azzakiyyah in Cinunuk, Bandung Regency, with the aim of improving educational quality. The research method employed a qualitative approach, utilizing interviews and literature reviews to understand the strategic steps taken by the institution. In the context of the research background, the importance of sustainable financing policies as a foundation for improving educational quality is discussed. The study delves into the implementation of these policies, identifies obstacles, and evaluates their impact on the educational quality at MTs Sains Qurani Azzakiyyah. The research findings highlight a close relationship between successful implementation and the involvement of various stakeholders, financial transparency, and strategic adaptation to environmental changes. Additionally, the study provides practical recommendations to enhance financial management policies and implementation for increased effectiveness in improving educational quality. The conclusion of this article is expected to contribute significantly to practical and theoretical understanding in the development of educational financing policies focused on enhancing educational quality, especially in secondary education institutions such as MTs Sains Qurani Azzakiyyah. Keywords: Policy, Financing, Educational Quality.